Prediction model investigations of the reinforced fine-grained tailings dam overtopping failure - Chen, Meibao; Jing, Xiaofei; Xie, Dongxu; Li, Xiaoshuang; Zhang, Yuanzhen; Liu, Xiaohua (Frontiers in Earth Science, 2023)
Overtopping failure of tailings dam will cause serious consequences; at present, the overtopping process of reinforced tailings dam cannot be well predicted. Therefore, establishing the overtopping prediction model of the reinforced tailings dam is significant. In this paper, the anti-erosion and anti-collapse effects of the fine-grained tailings dam after adding the reinforcement belt are considered, and the mathematical model of the breach development of the reinforced fine-grained tailings overtopping dam is established. In the model, the formula of supported erosion rate is obtained using the water flow shear stress principle; the development of breach erosion is simulated by the time iterative calculation method, and the stability of the reinforced breach slope is analyzed by the limit equilibrium method. The mathematical model was validated by a physical model experiment which reproduces the dam break of the fine-grained tailings dam. The breach development and discharge process are monitored, and the maximum breach depth and width agree with the calculated values by the mathematical model. The calculation results of the mathematical model established in this paper can help to predict the consequences of overtopping failure of the reinforced fine-grained tailings dam.